Analysis of Social Networks and Peer Contagion in Terrorism-Related Offences in Indonesia - Susetyo, Heru; Arimbi, Reisa Suci; Andersen, Morten Koch; Wang, Shr-Jie (Faculty of Law, Universitas Negeri Semarang, 2026)
This article addresses a timely and important issue: terrorism recruitment and disengagement in the digital era. It explores the intricate dynamics of social networks and peer contagion and their role in processes of recruitment and disengagement in terrorism activities in Indonesia. It emphasizes on how close relations and peers significantly influence young individual behavior, often facilitated through digital spaces; social media, encrypted chat groups, and other content-sharing platforms, and explores potential avenues for prevention and disengagement. The research is based on in-depth interviews with 20 former inmates convicted of acts of terrorism between 2023 and 2025 in the greater Jakarta and west Java region, Indonesia. The finding highlights that social networks serve as critical outreach platforms, especially for the young people, for disseminating extremist ideologies, sharing biased information and propaganda content, and serve to promote recruitment for violent activities. It demonstrates how communication and information sharing via digital spaces platforms plays a crucial role in shaping the processes that lead young individuals towards violent ideologies and practices. In addition, we observed that on one hand peer influence plays a pivotal role in enabling recruitment but on the other hand for prevention and disengagement efforts; although, antisocial and violent behavior spreads more readily than prosocial behavior among peers. Analysis indicate that a clear understanding of the structure of these social networks and their dynamics, as well as the mechanisms of peer contagion is essential for developing effective preventive strategies and targeted interventions. Importantly, these findings have broader practical implications, which not only provides insights of contextual complexities of recruitment and disengagement that could inform future research , but also for policymakers and practitioners who could translate this knowledge into policies and develop interventions that strengthen protective social ties, foster trust and support among peers, and guide the responsible use of digital spaces in Indonesia, and beyond. Ultimately, this study recommends revising the terrorism law in Indonesia regarding digital literacy and responsible supervision of digital space to prevent the spread of radicalism through digital space.